Assessment of Examination anxiety among undergraduate Students at Public Sector Nursing College, Jamshoro - Sabiha Sarwar; Tasleem bibi; Farzana Parveen; Irum Qureshi; Hafsa Bibi; Rozina Khowaja (Medical Journal of South Punjab, 2024)
Objective: To identify anxiety levels between undergraduate nursing students’ and examine the impact of this anxiety on their academic performance. Methods: A cross-sectional study was carried out at Liaquat College of Nursing Female Jamshoro (LCON) during the period of May 15,2023 to June 15,2023. Data of 103 nursing students were collected by using Westside anxiety scale to assess the anxiety score. Descriptive analysis, such as frequency counts and corresponding percentages was done, in addition non-parametric test to look at the relationship between two variables. Results: 103 Female participants completed the study. 54(52.4%) participant showed high test anxiety, 38(36.9%) participant showed moderately high test anxiety, 9(8.7%) participant showed high normal test anxiety, 2(1.9%) participant showed average test anxiety. The Fisher’s Exact Test shows statistically noteworthy correlation between CGPA and Examination anxiety score with P-value = 0.004, that means Test anxiety have great impact on student’s academic performance. Conclusion: The study’s findings indicated that a notable proportion of the students who took part in the research encountered moderate to severe levels of examination anxiety. It is important for assisting nursing undergraduate to cope with examination anxiety and identifying the triggers for it. Test anxiety can be effectively reduced through collaborative tasks including students, parents, educators, academic advisors, and other involved individuals. Nursing students should have access to counseling services when required.